Mother Knowledge and Attitudes towards Choking First Aid for Children 0-5 Years Old - Nurhayati, Resti; Emaliyawati, Etika; Mirwanti, Ristina (Universitas Padjadjaran, 2025)
Choking in toddlers can be fatal, underscoring the importance for mothers to be well-versed in first aid and to exhibit a supportive attitude when responding. However, there are still gaps in mothers' understanding of proper first aid techniques and psychological factors that influence their responses in emergency situations. This study aims to determine mothers' knowledge and attitudes regarding jfirst aid for choking children. The research design was descriptive quantitative with Cross Sectional approach. The sample in this study was 100 mothers. The sampling techniques used are proportional sampling and convenience random sampling. The researched collected data in January 2024 using knowledge and attitude questionnaires, and then analyzed using univariate analysis. The results showed 66% of participants answered important statements incorrectly, namely first aid for choking by only giving a drink, 43% of participants answered abdominal thrust is not the first aid for choking in children over 1 year old. Participants' attitudes showed that 97% would give back blow or abdominal thrust, and 81% would give chest trust. The conclusion of this study is that the mother's knowledge is lacking in several crucial statements regarding choking management, although the attitude of most mothers agrees to provide back blow, abdominal thrust and chest thrust actions, so education, simulation and training are still needed. For further research, it can compare whether there is an increase in knowledge and attitudes after providing education and training according to the needs of mothers in handling choking.